Diseño e implementación de un sistema de monitoreo y adquisición de datos en la cámara de transformación No. 2 para evaluar los índices de consumo de energía eléctrica en la Universidad Técnica de Cotopaxi Campus Matriz, período 2019-2020. - Achote Guanotásig, Guido José (2020)
This technological proposal is focused on the design of a procurement system of data and the implementation of equipment for monitoring and control, whose objective is to obtain data on the indices of electric power consumption, which will have a historical database and therefore to visualize the energy consumption values in the morning, evening and night journeys, in the transformation chamber, on the other hand, the monitoring of energy consumption rates benefits to the university and to the students as well since it will be possible to visualize the data obtained in any place through of a virtual platform. The data adquisition system consists of two fundamental elements such as the PM5110 power meter which allows measurement of electrical magnitude values such as power, frequency and current, on the other hand the EGX150 gateway which allows to link to a server through a web browser and an Ethernet network, besides that to be able to register and display the values in real time. It is for this reason that the implementation of the system will allow teachers, students and authorized personnel to obtain real-time data on a website, from the electrical quantities for the study of energy quality in the chamber of transformation number two of the Technical University of Cotopaxi campus Matriz, of the Cotopaxi Province. Finally, it was possible to show the consumption rates of the laboratories of the Technical University of Cotopaxi through the analysis of the electrical quantities and with the selected data a comparison was made with another network analyzer to determine the harmonics affected in the electrical network and with This can be analyzed in different changes in electrical engineering.